2017
DOI: 10.1016/j.scr.2017.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Human neural progenitors derived from integration-free iPSCs for SCI therapy

Abstract: As a potentially unlimited autologous cell source, patient induced pluripotent stem cells (iPSCs) provide great capability for tissue regeneration, particularly in spinal cord injury (SCI). However, despite significant progress made in translation of iPSC-derived neural progenitor cells (NPCs) to clinical settings, a few hurdles remain. Among them, non-invasive approach to obtain source cells in a timely manner, safer integration-free delivery of reprogramming factors, and purification of NPCs before transplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 94 publications
(125 reference statements)
2
29
0
Order By: Relevance
“…A possible explanation for this might be that iPSC are one of the most widely used cell types for transplantation performed to recover the functions impaired as a result of injury [32]. In addition, the mechanism by which iPSC transplantation mediated functional improvements after SCI is multifaceted [33][34][35] although it is commonly accepted that iPSC transplantation can [7]: 1) reduce the area of syringomyelia and increase the area of spared tissue; 2) promote local microvascular regeneration and nerve regeneration for the repair of damaged cells; 3) reduce inflammation and inhibit oxidative stress after SCI; and 4) improve axonal growth and reconstruction of neural pathways by secreting substrates. Moreover, our findings are consistent with the data obtained in the study reported by Führmann et al, which demonstrated that transplantation of pluripotent stem cells and their differentiated progeny has the potential to regenerate functional pathways and improve locomotor function after SCI [36].…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for this might be that iPSC are one of the most widely used cell types for transplantation performed to recover the functions impaired as a result of injury [32]. In addition, the mechanism by which iPSC transplantation mediated functional improvements after SCI is multifaceted [33][34][35] although it is commonly accepted that iPSC transplantation can [7]: 1) reduce the area of syringomyelia and increase the area of spared tissue; 2) promote local microvascular regeneration and nerve regeneration for the repair of damaged cells; 3) reduce inflammation and inhibit oxidative stress after SCI; and 4) improve axonal growth and reconstruction of neural pathways by secreting substrates. Moreover, our findings are consistent with the data obtained in the study reported by Führmann et al, which demonstrated that transplantation of pluripotent stem cells and their differentiated progeny has the potential to regenerate functional pathways and improve locomotor function after SCI [36].…”
Section: Discussionmentioning
confidence: 99%
“…Integration-free neural progenitor cells generated by reprogramming of epithelial-like cells from human urine can be differentiated into multiple functional neuronal and glial subtypes in vitro [48]. Recent data obtained in experimental animal models showed that reprogrammed integrationfree iPSCs derived from human neural progenitors collected from urine differentiated into neurons and glia within 8 weeks of being transplanted into contused mouse thoracic spinal cords, though the study lacked functional data with respect to SCI recovery and included the oncogene c-Myc in its reprogramming protocol [49].…”
Section: (4) Reprogrammed Stem Cells Since 2006 Whenmentioning
confidence: 99%
“…Out of a total of 22 reports that assessed iPSC‐derived neural cells for SCI treatment, the following studies were incorporated into the meta‐analysis . A few studies were excluded, because statistical significance could not be verified, motor recovery was not assessed, used a different scale to assess motor recovery, or focused on a cervical SCI model. Other studies were conducted in primates using iPSCs, and insufficient data were provided to perform a separate t ‐statistic.…”
Section: Resultsmentioning
confidence: 99%